Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank Group (World Bank, Washington, DC, 2019)
The main body of the report is organized in two chapters and two supporting annexes. Chapter I focuses on recent economic developments in the real, fiscal and banking sectors, while providing a near term outlook that highlights critical challenges facing the Palestinian economy. Chapter II looks at the impact of dual use restrictions on specific sectors in both the West Bank and Gazan economies and makes short and long run recommendations that would allow more activity and job creation. Annex 1 assesses the status of the World Bank recommendations to the AHLC meeting over the years, while Annex 2 has details of the dual use restrictions that are currently in place.